Differentiation and Genetic Studies of Several Isolates of Cucumber Mosaic Virus - El-Sanousi, Omar Mussa (1997)
Four cucumber mosaic Virus (CMV) isolates from different host and localities were differentiated on the basis of biological and serological properties and polymerase chain reaction (PCR). The first two isolates (CMV-3 and CMV-7) were isolated from tobacco in Telong, Kelantan; the third (CMV-4) was from chilli in MARDI lalan Kebun, Klang and the fourth isolate (CMV-6 ) was from purple cleome in Sri Kembangan, Selangor. These isolates could be distinguished from each other by the symptoms produced in several plant species. CMV-3 and CMV-7 were more similar to each other than to the other isolates. Aphid transmission test revealed that all the isolates could be transmitted by A. gossypii with higher efficiency than A. craccivora. Immunodiffusion tests revealed that all the isolates were closely related since all the heterologous titres were within the same two-fold dilutions of each other. In the DAS-ELISA tests, there were variations observed between the homologous and the heterologous antigens which revealed that the isolates CMV-3, -6, -7 had a closer relationship to each other than to CMV-4; and the isolate CMV-7 had a more distant relationship to isolate CMV-4 than to the others. All the isolates showed a closer relationship to D strain (DTL serogroup) but could not be detected by Q strain (ToRS serogroup) when the DAS-ELISA was used. By indirect-ELISA, all the isolates could be detected by D and Q strains. A single band of about 487 bp were successfully amplified from the coat protein gene of the CMV isolates. The PCR product could be digested by Msp I to produce two bands of approximately 337 and lSI bp but could not be digested by EcoR 1. Result of analysis of the biological and serological properties as well as PCR confirmed that the isolates belonged to subgroup I of CMV. To detennine the gene or genes location of symptoms determinants in the RNA segments, six pseudo recombinants were constructed in vitro between the RNAs of CMV-4 and CMV-3; and two pseudorecombinants by exchanging RNA3 between CMV-4 and CMV-7. The observations on chilli cv. MC4, tomato cv. Eggtomato, N. glutinosa and N. tabacum cv. White Burley infected with these pseudorecombinants indicated that RNA 2 or 3 or both were involved in symptoms production. Two different types of sat-RNA, named sat-RNA6 and sat-RNA7 were found to be naturally associated with CMV-6 and CMV-7, respectively. The association of these sat- RNAs with the CMV isolates reduced the virus concentration up to ten times. These sat-RNAs induced systemic necrosis in tomato and attenuated the symptoms produced by the genomic RNAs in MC4 chilli and White Burley tobacco. Sat-RNA6 showed a higher virulence by inducing systemic necrosis in tomato and produced local necrosis in inoculated White Burley tobacco leaves.